Слов’янські пам’ятки на Тернопільщині - Ягодинська, М.О. (Археологія і давня історія України, 2020)
Розглянуто пам’ятки празької та райковецької культури, відкриті на території міста Теребовля та в її околицях. Наведено характеристику досліджених жител та господарських споруд, проаналізовано керамічний посуд, знайдений в закритих комплексах поселень. Дана коротка характеристика стану вивчення слов’янських пам’яток в межиріччі Дністра та Вілії. The article deals with the situation of Slavic sites study in the Ternopil region. By chronology the Slavic sites divide into 2 periods: the early (second half of the 5th—7th centuries) connected with time of the existence of the Prague culture, and the later (8th — first half of the 10th centuries) — the time of the existence of Raikovetska culture. Special attention is paid to the hill-forts and settlements near Terebovlia.